Effect of calcium chloride on the pH values of several formulations of calcium hydroxide mixed with chlorhexidine digluconate - Marins-de-Azevedo, Hemanoely; Montenario, Rodrigo Vargas Conti; Crespo, Mariana Pires; Kuga, Milton Carlos [UNESP]; Nascimento, Camila Almeida (My University, 2013)
This study evaluated the effect of the addition of 5% calcium chlorite (CaCl2) on pH values in calcium hydroxide pastes (CH), with or without 2% chlorhexidine digluconate (CHX) used as vehicle, in several periods analysis. Polyethylene tubes were filled with CH mixed with water (G1), 2% CHX solution (G2) or gel (G3), or CHX solution or gel with 5% CaCl2 (G4 and G5, respectively). All tubes were individually immersed in distilled water. After 12, 24 hours, 7, 14 and 28 days, pH value was evaluated directly in water which the tubes were stored. Data were submitted to ANOVA and Tukey tests (α=0.05). In 24 hs and 14 days, pH values were similar to all groups. In 12 hs, the G1 presented lower pH value than other groups except to G4 (p < 0.05), and G4 presented lower pH value than G5 (p < 0.05). In 7 days, G1 presented lower pH value than G4 and G5 (p < 0.05). In 28 days, G1 and G5 presented lower pH values than G2 and G4 (p < 0.05) and among other groups there are no statistical differences (p > 0.05). The pH values increased in long-term analysis to all CH pastes. The association of 5% calcium chloride with 2% CHX solution as vehicle of CH paste provided a pH value increase in relation to CH mixed with distilled water. The CHX gel interfered negatively on pH value in comparison to CHX solution when mixed with CaCl2.
Keywords: Calcium; Chlorhexidine; Hydrogen; pH